Implementation of Computer Assisted Test Selection System in Local Governments (Jurnal Bina Praja, 2016)
As an evaluative way of selection of civil servant system in all government areas, Computer Assisted Test selection system was started to apply in 2013. In phase of implementation for first time in all areas in 2014, this system selection had trouble in several areas, such as registration procedure and passing grade. The main objective of this essay was to describe implementation of new selection system for civil servants in the local governments and to seek level of effectiveness of this selection system. This essay used combination of study literature and field survey which data collection was made by interviews, observations, and documentations from various sources, and to analyze the collected data, this essay used reduction, display data and verification for made the conclusion. The result of this essay showed, despite there a few parts that be problem of this system such as in the registration phase but almost all phases of implementation of CAT selection system in local government areas can be said was working clearly likes in preparation, implementation and result processing phase. And also this system was fulfilled two of three criterias of effectiveness for selection system, they were accuracy and trusty. Therefore, this selection system can be said as an effective way to select new civil servant. As suggestion, local governments have to make prime preparation in all phases of test and make a good feedback as evaluation mechanism and together with central government to seek, fix and improve infrastructures as supporting tool and competency of local residents.
Keywords: CAT system; local governments; civil servants